2016
DOI: 10.1111/jcmm.13005
|View full text |Cite
|
Sign up to set email alerts
|

Morin hydrate promotes inner ear neural stem cell survival and differentiation and protects cochlea against neuronal hearing loss

Abstract: We aimed to investigate the effect of morin hydrate on neural stem cells (NSCs) isolated from mouse inner ear and its potential in protecting neuronal hearing loss. 3‐(4,5‐dimethyl‐2‐thiazolyl)‐2,5‐diphenyl‐2‐H‐tetrazolium bromide (MTT) and bromodeoxyuridine incorporation assays were employed to assess the effect of morin hydrate on the viability and proliferation of in vitro NSC culture. The NSCs were then differentiated into neurons, in which neurosphere formation and differentiation were evaluated, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In that respect, organotypic culture of cochlear explants have strong advantages to explore the underlying mechanisms for a particular pathogenesis or development, because the cultured cochlear explants have been proven to maintain intact conformation of the hair cells and neuronal innervation with following normal processes of development during it is cultured [46] , [47] . Importantly, most of hearing loss studies that performed both ex vivo and in vivo experiments have shown strong consistency in the results between these two systems [48] , [49] , [50] , [51] , which suggest that ex vivo studies also could provide significant and reliable massages.…”
Section: Discussionmentioning
confidence: 96%
“…In that respect, organotypic culture of cochlear explants have strong advantages to explore the underlying mechanisms for a particular pathogenesis or development, because the cultured cochlear explants have been proven to maintain intact conformation of the hair cells and neuronal innervation with following normal processes of development during it is cultured [46] , [47] . Importantly, most of hearing loss studies that performed both ex vivo and in vivo experiments have shown strong consistency in the results between these two systems [48] , [49] , [50] , [51] , which suggest that ex vivo studies also could provide significant and reliable massages.…”
Section: Discussionmentioning
confidence: 96%
“…Morin (2′,3,4′,5,7-pentahydroxyflavone) is rich in mulberry leaves, which are widely planted in the South China region . A large amount of evidence suggests that morin has various pharmacological effects, such as anti-cancer, anti-inflammation, and inhibition of apoptosis. Although morin has been reported to repair chronic experimental colitis, mechanisms that regulate the regenerative response of the intestinal epithelium upon injury remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Morin, a natural bioflavonoid originally isolated from members of the Moraceae family, has been reported to possess antiinflammatory, antioxidant, anticancer and neuroprotective properties (Caselli, Cirri, Santi, & Paoli, 2016; Sharma, Kumar, Chellappan, & Nagarajan, 2018; Sinha, Sadhukhan, Saha, Pal, & Sil, 2015; Zhao et al, 2017). Morin protects neural stem cells in the mouse inner ear in an in vitro ototoxicity model (He, Jia, Zhang, & Ren, 2017). In vivo, morin alleviates hippocampal neuron damage in REM sleep‐deprived mice (Olonode, Aderibigbe, Adeoluwa, Eduviere, & Ben‐Azu, 2019).…”
Section: Introductionmentioning
confidence: 99%